2012
DOI: 10.3329/jhpn.v30i2.11310
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Complications and Psychological Well-being: Experiences of Bangladeshi Women during Pregnancy and Childbirth

Abstract: Women in developing countries experience postnatal depression at rates that are comparable with or higher than those in developed countries. However, their personal experiences during pregnancy and childbirth have received little attention in relation to postnatal depression. In particular, the contribution of obstetric complications to their emotional well-being during the postpartum period is still not clearly understood. This study aimed to (a) describe the pregnancy and childbirth experiences among women i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 30 publications
5
30
0
Order By: Relevance
“…Since 2006, a methodologically strong study ( n =55,814) by Adams et al (2012) has corroborated this null relationship between mode of delivery and elevated symptoms of depression. Similarly, most authors report no increased likelihood of elevated symptoms of depression after exposure to birth complications or interventions; however, studies differ widely in their defining variables and how variables are scored (e.g., labor dystocia, eclampsia, infection, epidural, artificial rupture of membranes, labor induction/augmentation, episiotomy, hemorrhage, newborn in special care) (Blom et al 2010; Fairbrother and Woody 2007; Fisher et al 1997; Gausia et al 2012; Johnstone et al 2001; Murray and Cartwright 1993; Rowe-Murray and Fisher 2001). Only a few authors have reported on elevated symptoms of depression after exposure to labor pain medication; findings are inconsistent and inconclusive due to wide variation in sample size, assessment of antenatal mood, and bivariate versus multivariate analyses (Astbury et al 1994; Hiltunen et al 2004; Righetti-Veltema et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since 2006, a methodologically strong study ( n =55,814) by Adams et al (2012) has corroborated this null relationship between mode of delivery and elevated symptoms of depression. Similarly, most authors report no increased likelihood of elevated symptoms of depression after exposure to birth complications or interventions; however, studies differ widely in their defining variables and how variables are scored (e.g., labor dystocia, eclampsia, infection, epidural, artificial rupture of membranes, labor induction/augmentation, episiotomy, hemorrhage, newborn in special care) (Blom et al 2010; Fairbrother and Woody 2007; Fisher et al 1997; Gausia et al 2012; Johnstone et al 2001; Murray and Cartwright 1993; Rowe-Murray and Fisher 2001). Only a few authors have reported on elevated symptoms of depression after exposure to labor pain medication; findings are inconsistent and inconclusive due to wide variation in sample size, assessment of antenatal mood, and bivariate versus multivariate analyses (Astbury et al 1994; Hiltunen et al 2004; Righetti-Veltema et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, many studies suggest that the likelihood of elevated symptoms of depression is lower in women reporting birth as a positive birth experience (Gausia et al 2012; Giakoumaki et al 2009; Gurber et al 2012; Sorenson and Tschetter 2010; Weisman et al 2010), greater labor support from care providers (Cigoli et al 2006; Sorenson and Tschetter 2010), greater involvement with labor management decisions (Green and Baston 2003; Green et al 1990), and a less difficult birth (Tuohy and McVey 2008), although the studies typically did not control for antenatal symptoms of depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Another study in rural area of Bangladesh revealed that highest respondents had primary education. 17 This inconsistent finding might be due to the difference of selection of study places. In the view of economic condition, more (7.1%) psychiatric disorders were found in the income group more than 15000 TK.…”
Section: Thismentioning
confidence: 74%
“…In addition to research on postpartum conditions, literature is accumulating about the effects of birth complications on depressive symptoms. In Asia, pregnancy complications, negative childbirth experiences, and severe morbidity at the time of childbirth have been associated with subsequent postpartum depressive symptomatology (Gausia et al, 2012; Giri et al, 2015; Lyengar, Yadav, & Sen, 2012; Shivalli & Gururaj, 2015). Some studies, however, have not found a significant relation between severe medical complications during or immediately after pregnancy with postpartum depressive symptoms, perhaps because the occurrence of severe morbidity is quite rare (Norhayati, Nik Hazlina, Aniza, & Asrenee, 2016).…”
Section: Discussionmentioning
confidence: 99%